The Effect of Cash Flow on Liquidity Levels at PT. Wijaya Karya (Persero) Tbk on the Indonesian Stock Exchange - Nurjihanar, Nurul Mutmainnah; Ruma, Zainal; Anwar (PT. Maju Malaqbi Makkarana, 2022)
This research aims to determine the effect of cash flow on the level of liquidity at PT. Wijaya Karya (Persero) Tbk on the Indonesian Stock Exchange. The type of research used is descriptive quantitative. The research population is the financial statements of PT. Wijaya Karya (Persero) Tbk for 5 (five) periods, namely 2015-2019. The samples for this research are the balance sheet, profit and loss report and cash flow report of PT. Wijaya Karya (Persero) Tbk for 5 (five) periods, namely 2015-2019. The data in this research is secondary data with data collection techniques using documentation methods for company financial reports. The data analysis technique uses multiple linear regression analysis.Partial research results (t test) state that partial operating cash flow does not have a significant effect on liquidity. Meanwhile, the investment cash flow variable partially has a significant effect on the level of liquidity. And the partial funding cash flow variable has no significant effect on liquidity. Simultaneous research results (F test) state that operating cash flow, investment cash flow and funding cash flow have a value of Fcount > Ftable (3.275 > 2.95) and a significance value of < 0.05 (0.003 < 0.05), So it can be concluded that the operating cash flow, investment cash flow and funding cash flow variables simultaneously have a significant effect on the level of liquidity.